Political Ecology System Change Not Climate Change - Roussopoulos, Dimitri (Black Rose Books, 2018)
"In this new and greatly expanded edition of his 1991 classic Political Ecology, Dimitri Roussopoulos delves into the history of environmentalism to explain the failure of the State's management of the ecological crisis. He explores civil society's various past responses and the prospects for channeling environmentalist aspirations into political alternatives, emphasizing the ideas of social ecology and the central role of democratic neighborhoods and cities in developing alternatives. Ecologists, Roussopoulos argues, aim for more than simply protecting the environment- they call for new communities, new lifestyles, and a new way of doing politics."--